2007
DOI: 10.1186/1475-2875-6-99
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of male reproductive success in a laboratory population of Anopheles gambiae

Abstract: Background: For Anopheline mosquitoes, the vectors of human malaria, genetic variation in male reproductive success can have important consequences for any control strategy based on the release of transgenic or sterile males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…This study emphasizes the importance of partitioning male reproductive success into its constituent components such as insemination success, oviposition success, and the number of eggs per batch [e.g. [ 45 ]]. Female oviposition is generally conditional on the female having been inseminated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study emphasizes the importance of partitioning male reproductive success into its constituent components such as insemination success, oviposition success, and the number of eggs per batch [e.g. [ 45 ]]. Female oviposition is generally conditional on the female having been inseminated.…”
Section: Discussionmentioning
confidence: 99%
“…These two observations suggest that the quality or quantity of the male ejaculate influenced female oviposition. Using the G3 strain of A. gambia , it was previously shown that males vary genetically in their ability to induce females to oviposit [ 45 ]. The present study suggests a mechanistic link between sperm motility and oviposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, lek‐based mating system is often characterized by a high skew in male mating success (Mackenzie et al 1995). Possible factors accounting for this mating bias are male body size (Yuval et al 1993, Voordouw and Koella 2007, Huho et al 2007), age (Chambers and Klowden 2001, Huho et al 2006, 2007), genetics (Voordouw and Koella 2007), sperm length (Voordouw and Koella 2007) and energetic reserves (Yuval et al 1994, Huho et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many examples of body size and higher fitness have been reported in mosquitoes in relation to malemating success (Ponlawat andHarrington 2009), survival (Maciel-De-Freitas et al 2007) or even towards egg production and female feeding behavior (Takken et al 1998;Voordouw and Koella 2007;Xue et al 1995b). Hence, the larger body size of the four transgenic mosquito strains studied here could imply in a fitness advantage in the field, with an increased possibility of local dissemination among the local population.…”
Section: Materials Results and Discussionmentioning
confidence: 95%